2010
DOI: 10.1111/j.1365-2125.2010.03639.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approaches to methamphetamine dependence: a focused review

Abstract: Methamphetamine dependence is a serious worldwide public health problem with major medical, psychiatric, socioeconomic and legal consequences. Various neuronal mechanisms implicated in methamphetamine dependence have suggested several pharmacological approaches. A literature search from a range of electronic databases (PubMed, EMBASE, PsycInfo, the NIDA research monograph index and the reference list of clinicaltrials.gov) was conducted for the period from January 1985 to October 2009. There were no restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
182
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(188 citation statements)
references
References 131 publications
(133 reference statements)
0
182
0
6
Order By: Relevance
“…With continued interest in modafinil as a potential pharmacotherapy for stimulant abuse (Karila et al, 2010), our results indicate that improvements in cognitive function elicited by the medication may augment traditional behavioral therapies and increase their efficacy. Modafinil or other cognition-enhancing medications may therefore be useful adjuncts to behavioral treatments for stimulant dependence.…”
Section: Discussionmentioning
confidence: 84%
“…With continued interest in modafinil as a potential pharmacotherapy for stimulant abuse (Karila et al, 2010), our results indicate that improvements in cognitive function elicited by the medication may augment traditional behavioral therapies and increase their efficacy. Modafinil or other cognition-enhancing medications may therefore be useful adjuncts to behavioral treatments for stimulant dependence.…”
Section: Discussionmentioning
confidence: 84%
“…Methamphetamine (METH) is one of most prevalent addictive central nervous system (CNS) stimulant drugs (Cruickshank and Dyer, 2009;Krasnova and Cadet 2009;Karila et al, 2010;Marshall and O'Dell, 2012). Recent studies have suggested that METH is a neurotoxic drug that can cause pathological changes and death in neuronal and glial cells (Thompson et al, 2004;Kitamura et al, 2007Kitamura et al, , 2010Takeichi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The withdrawal syndrome will be peaked within 2-4 days and will eliminate after a week and depression associated with suicidal ideation and attempts are the most important symptoms of abstinence (5). The efficiency of pharmacological intervention for treatment of Methamphetamine related disorders is not clear yet (2,12). Different drugs such as sertraline, bupropion, mirtazapine, Modafinil, Dextroamphetamine, Ondansetron, Risperidone, Aripiprazole, Baclofen, Gabapentin and Nalterxon as a treatment of methamphetamine-related disorders were examined, it has been reported that Aripiperazol is the most common drug used (1,12).…”
mentioning
confidence: 99%